Застосунки для створення ілюстрації на IPAD - Астахова, А. А. (ХНУРЕ, 2023)
This article discusses various apps for creating illustrations on iPad, comparing their features and suitability for different types of artwork. The article covers a range of apps, including industry standards like Adobe Illustrator, as well as specialized apps like Procreate, Art Set, Adobe Photoshop, Adobe Illustrator, Vectornator, and IbisPaint X. It explores each app's drawing tools, user interface, and compatibility with the Apple Pencil. The article concludes with a summary of key considerations when choosing an illustration app for iPad.
Keywords: iPad; ілюстрація